A wide tunable fast settling 4-bit digitally controlled oscillator for reconfigurable multi-band RF applications. (October 2019) - S., Aditya; Sridharan, Moorthi
Abstract: A digitally tunable differential active inductor based 4-bit digitally controlled oscillator to reduce the area and cost, for reconfigurable multi-band RF applications is proposed in this work. This design attains coarse frequency tuning of 0.571–3.74 GHz for digital control word 1 to 15 with percentage tuning range (%TR) of 147.02%. The noise analysis shows phase noise of −95.5 to −100.5 dBc/Hz @ 5 MHz offset with power consumption varying from 1.02 to 9.5 mW. The design achieves Figure-of-merit (FOM) of −146.07 dBc/Hz and Figure-of-merit with %TR (FOMT ) of −169.416 dBc/Hz. The proposed design occupies an area of 44 μm × 18 μm in standard 180 nm CMOS technology. A thorough post layout analysis of the design including the parasitic RC components to test the DCO stability over process, voltage and temperature variations (PVT), has been carried out and the results are plotted.